A SPEECH ACT ANALYSIS OF TEACHER’S UTTERANCES - Bagus Alghani; Melinda Roza (Universitas Nahdlatul Ulama Lampung, 2019)
The objective of this study is to analyze the speech act types employed by an ESL teacher. The researcher investigated the utterances using qualitative analysis. There were two classes examined with different materials on the same teacher. The results indicated that the teaching learning process committed at SMPN 1 Purbolinggo showed a preponderance of “Representatives”. The Representatives showed preponderance to explain the subjects and assert suggestions. Thus, Representative is highly recommended as an effective speech act type used to study a lesson.